Does previous history of cancer or atypia predict histologic upgrade for pure intraductal papillomas diagnosed via core biopsy? A study of 490 cases at a single institution. Issue 3 (2nd November 2021) - Alberty‐Oller, J. Jaime; Reyes, Sylvia; Moshier, Erin; Ru, Meng; Weltz, Sarah; Santos, Antonio; Pisapati, Kereeti; Port, Elisa; Jaffer, Shabnam
Abstract: Background: Management of pure intraductal papillomas (IDP) without atypia diagnosed on core needle biopsy (CNB) remains controversial given highly variable rates of upgrade in the literature. Aim: We sought to identify clinical and histologic factors that predict upgrade to atypia or malignancy in a large population. Methods and results: A retrospective review was performed of all cases of pure IDP diagnosed on CNB and then surgically excised at a single institution from 2008 to 2018. Clinical, radiologic, and pathologic factors were compared in the no upgrade, upgrade to atypia, or upgrade to cancer groups. Univariate analysis was performed comparing no upgrade and upgrade to cancer or atypia. Four hundred and thirty nine patients were identified with a total of 490 IDP and a median age of 50 years (range 16–85). Of these patients, 54 (12.3%) were upgraded to atypia after surgical excision and five (1.1%) were upgraded to cancer. The presence of multiple papillomas in a single patient was a significant predictor of upgrade to cancer or atypia ( p  < .01), as well as age over ≥55 years ( p  < .01) and a prior history of cancer ( p  < .01). No other clinical, radiologic and histologic factors were found to be significant predictors of upgrade. 40/439 (9.1%) patients in the total cohort had prior history of cancer, and of these, 2/40 (5%) were found to have a new cancer after excision. Conclusions: In patients with pure IDP on CNB, the upgrade rate to malignancy was 1.1%, while 12.3% were upgraded to atypia. The clinical significance of identifying atypia in a papilloma is unknown, especially in a patient with a prior history of atypia or cancer. However, the majority of patients who were upgraded to either atypia or cancer had no prior history of high‐risk or malignant breast disease and are therefore considered true clinical upgrades. As such excision for IDP should be considered.